Dynamics of Bacteriorhodopsin in the Dark‐Adapted State from Solution Nuclear Magnetic Resonance Spectroscopy. (7th September 2020) - Kooijman, Laurens; Schuster, Matthias; Baumann, Christian; Jurt, Simon; Löhr, Frank; Fürtig, Boris; Güntert, Peter; Zerbe, Oliver
Abstract: To achieve efficient proton pumping in the light‐driven proton pump bacteriorhodopsin (bR), the protein must be tightly coupled to the retinal to rapidly convert retinal isomerization into protein structural rearrangements. Methyl group dynamics of bR embedded in lipid nanodiscs were determined in the dark‐adapted state, and were found to be mostly well ordered at the cytosolic side. Methyl groups in the M145A mutant of bR, which displays only 10 % residual proton pumping activity, are less well ordered, suggesting a link between side‐chain dynamics on the cytosolic side of the bR cavity and proton pumping activity. In addition, slow conformational exchange, attributed to low frequency motions of aromatic rings, was indirectly observed for residues on the extracellular side of the bR cavity. This may be related to reorganization of the water network. These observations provide a detailed picture of previously undescribed equilibrium dynamics on different time scales for ground‐state bR. Abstract : Nuclear magnetic resonance (NMR) spectroscopy was employed to monitor methyl relaxation in the side chains of the light‐driven proton pump bacteriorhodopsin (bR) and its less active M145A mutant. The findings provide a detailed picture of equilibrium dynamics on different time scales for ground‐state bR.